Employee's perception towards female managers leadership characteristics - Muninathan, Deebha. (Universiti Malaysia Sarawak (UNIMAS), 2003)
The purpose of this study is to detennine the perception of administrative staff in hotel towards female manager leadership characteristics and the factors that influence it. Specifically, the objectives of the study are to detennine if there is any difference among employees with varied socio-demographic characteristics, such as gender, academic qualification, years of service and position in terms of their perception towards female managers leadership characteristics. Another objective is to determine whether there is any significant relationship between female manager leadership characteristics and factors such as communication, coaching and problem solving. This study utilized the survey research methodology. The respondents were 40 administrative employees from six of four and five star hotels in Penang Island. Stratified sampling is used to detennine the minimum sample size required for the sample. The research instrument used was a questionnaire. Statistical tests carried out were the one-way ANOVA, independent sample t-test, and Pearson's Bivariate Correlation. The study found that the majority (92.5 %) of administrative employees in six hotels have a positive perception towards female manager leadership characteristics. The study also shows that there is a significant difference among administrative employees in terms of their perception towards female manager leadership characteristics based on their academic qualification (F=6.736, p=O.OOO) and position (t=2.547, p=0.015). this study also indicates that there is no significant difference between administrative employees in terms of their perception towards female manager leadership characteristics based on gender (t=1.423, p=0.163) and years of service (F=0.509, p=0.679). The Pearson Correlation Coefficient Analysis also revealed that there is significant relationship between female manager leadership characteristics and factors such as coaching (r=0.769, p<O.OI), communication (r=0.715, p<O.OI) and problem solving (r=0.888, p<O.OI). The findings of the study indicates that the female manager "leadership characteristic is influence by coaching, communication and problem solving.